Differences in Functional Loss Associated with Ganglion Cell Complex Thinning between Patients with Glaucoma and Postoperative Macular Hole. (August 2014) - Machida, Shigeki; Tamada, Kunifusa; Ohzeki, Takayuki; Gotoh, Yasutaka; Kurosaka, Daijiro
Abstract Purpose: To compare the changes in the photopic negative response (PhNR) of the focal macular electoretinogram (fmERG) caused by a thinning of the ganglion cell complex (GCC) between patients with open angle glaucoma (OAG) and after successful macular hole (MH) surgery. Methods: Twenty-seven eyes of 27 OAG patients (OAG group), 28 eyes of 28 MH patients (MH group) and 23 eyes of 23 normal volunteers (control group) were studied. The OAG patients had early stage of glaucoma. The MH patients had been successfully treated with vitrectomy 12 months earlier. The averaged GCC thickness in the macular area (15 degree in a diameter) was measured by SD-OCT. The fmERGs were elicited by a 15° stimulus centered on the fovea. Results: The GCC was significantly thinner in the OAG and MH groups than in the control group (p < 0.0001). The PhNR amplitude and PhNR/b-wave amplitude ratio were significantly reduced in the OAG group compared to the control (p < 0.0001), while no significant reduction of the PhNR amplitude was observed in the MH group. The PhNR amplitude and PhNR/b-wave amplitude ratio were significantly correlated with the GCC thickness in the OAG group (R2 = 0.741 for the PhNR amplitude, R2 = 0.564 for the PhNR/b-wave amplitude ratio, p < 0.0001 for both). There were significant differences in the slopes of regression lines plotting the GCC thickness and the PhNR amplitude (p < 0.05) or the PhNR/b-wave amplitude ratio (p < 0.0005) between the OAG and MH groups. Conclusions: The thinning of the GCC affects the RGC function in the macula area differently for patients with OAG and patients after MH closure.